2020
DOI: 10.1016/j.jesp.2019.103937
|View full text |Cite
|
Sign up to set email alerts
|

“Rarely safe to assume”: Evaluating the use and interpretation of manipulation checks in experimental social psychology

Abstract: The text of the preprint may differ slightly from the version of record.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 48 publications
0
56
0
Order By: Relevance
“…The scoping review revealed that over a third (35.67%) of studies within the review excluded participants on the basis of manipulation check, general memory check, or attention check questions included in their studies. This proportion of studies using this exclusion criterion exceeds the rates of studies employing this exclusion criterion in general social psychology research (Abbey & Meloy, 2017; Ejelöv & Luke, 2020). For some studies within the scoping review, exclusion rates were not modest, with a range from 0–34% of total participants excluded.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…The scoping review revealed that over a third (35.67%) of studies within the review excluded participants on the basis of manipulation check, general memory check, or attention check questions included in their studies. This proportion of studies using this exclusion criterion exceeds the rates of studies employing this exclusion criterion in general social psychology research (Abbey & Meloy, 2017; Ejelöv & Luke, 2020). For some studies within the scoping review, exclusion rates were not modest, with a range from 0–34% of total participants excluded.…”
Section: Discussionmentioning
confidence: 74%
“…However, this is what is often assumed. Manipulation checks and attention checks are treated as interchangeable (Ejelöv & Luke, 2020). Our review also highlighted this, with studies using inconsistent terminology to describe memory‐ and attention‐based questions, stating that memory‐based questions were included to assess participants' attention (and excluding on this basis).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations